Regulation of The Imposition of Criminal Sanctions against The Criminal Acts of Prostitution in Indonesian Positive Law - Ida Bagus Gumilang Galih Sakti; I Made Arjaya (Jurnal Hukum Prasada, 2022)
Prostitution activities that occur in society are not only caused by pimps and sex peddlers, but are also closely related to users of prostitution services. The absence of regulations that can ensnare perpetrators of prostitution practices, especially users of prostitution services, shows the government's inconsistency in combating prostitution practices. There are two problems in this study, namely, first, how is the regulation of punishment for perpetrators of criminal acts of prostitution in Indonesian positive law and second, how is the imposition of criminal sanctions against perpetrators of criminal acts of prostitution, especially users of prostitution services through complaint offenses in the Criminal Code. This study uses normative research conducted through an assessment of the legislation and legal concepts. The approach in this study uses a legal concept approach, and a statutory approach. Based on various explanations of articles in Indonesian positive law, it is not at all clear and implicit that there are articles that regulate criminal sanctions against users of prostitution services. With the absence of legal norms related to criminal sanctions for users of prostitution services, other legal remedies can be taken to ensnare users of prostitution services through the application of a complaint offense with the alleged crime of adultery as regulated in Article 284 of the Criminal Code.